A facile approach to chemically modified graphene and its polymer nanocomposites - Zaman, Izzuddin; Kuan, Hsu-Chiang; Meng, Qingshi; Michelmore, Andrew; Nobuyuki, Kawashima; Pitt, Terry; Zhang, Liqun; Gouda, Sherif; Lee, Luong; Jun, Ma (Wiley-VCH Verlag, 2012)
A scalable approach for the mass production of chemically modifi ed graphene has yet to be developed, which holds the key to the large-scale production of stable graphene colloids for optical electronics, energy conversion, and storage materials, catalysis, sensors, composites, etc. Here, a facile approach to fabricating covalently modifi ed graphene and its polymer nanocompos- ites is presented. The method involves: i) employing a common furnace, rather than a furnace installed with a quartz tube and operated in inert gas as required in previous studies, to treat a commercial graphite intercalation compound with thermal shocking and ultrasonication and fabricate graphene platelets (GnPs) with a thickness of 2.51 ± 0.39 nm that contain only 7 at% oxygen; ii) grafting these GnPs with a commercial, long-chain surfactant, which is able to create molecular entanglement with polymer matrixes by taking advantage of the reactions between the epoxide groups of the platelets and the end amine groups of the surfactant, to produce chemically modi- fi ed graphene platelets ( m - GnPs); and iii) solution-mixing m -GnPs with a commonly used polymer to fabricate nanocomposites. These m -GnPs are well dispersed in a polymer with highly improved mechanical properties and a low percolation threshold of electrical conductivity at 0.25 vol%. This novel approach could lead to the future scalable production of graphene and its nanocomposites.